2022
DOI: 10.1002/alz.062090
|View full text |Cite
|
Sign up to set email alerts
|

Computerized cognitive interventions for preventing dementia in people with mild cognitive impairment: A systematic review with meta‐analyses

Abstract: BackgroundPeople with mild cognitive impairment (MCI) are faced with a higher risk of developing dementia, but with a “window of opportunity” for prevention and treatment. Computerized cognitive interventions (CCIs) might constitute a beneficial non‐pharmacological treatment approach. This systematic review evaluated evidence of CCIs performed individually with a computer, tablet‐PC, game consoles, virtual reality (VR), or augmented reality (AR) on cognition in community‐dwelling people with MCI.MethodA system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With the contribution of today's digital technology, many online applications have started to be used in the topics of cognitive stimulation, training, and rehabilitation. Research results of programs targeting training and rehabilitation are discussed in various review articles [14,15]. Most studies reported that users do not need to be technologically skilled to successfully complete or benefit from training.…”
Section: Introductionmentioning
confidence: 99%
“…With the contribution of today's digital technology, many online applications have started to be used in the topics of cognitive stimulation, training, and rehabilitation. Research results of programs targeting training and rehabilitation are discussed in various review articles [14,15]. Most studies reported that users do not need to be technologically skilled to successfully complete or benefit from training.…”
Section: Introductionmentioning
confidence: 99%
“…Beside assistive technology, which is useful to build a bridge between the individual's functioning and the requirements of their daily environment, new technologies rely on the use of wearable technologies, mobile technologies, serious games, and telerehabilitation (Di Lorito et al, 2021 ; Bacanoiu and Danoiu, 2022 ; Robinson and Moghaddam, 2022 ). Furthermore, virtual reality (VR) setups may be used (Moon and Han, 2022 ; Zuschnegg et al, 2022 ; Jang et al, 2023 ). Computer-mediated interventions can make up for some of the disadvantages of traditional approaches.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported effect sizes of computerised training, domainspecific effects on memory, quality of life and long-term effects in people with MCI are still inconclusive ranging from no or little to large beneficial effects, sometimes with low-quality evidence. 17,18 Neuroplastic changes of the brain occur not only in early development but throughout the life-span and are related to injury as well as stimulation. 19 In the aging brain reduced brain plasticity with associated sensory and sensorimotor decline, noisy sensory processing, 20 changes in behaviour that accelerate cognitive decline, 21 disuse of sensorimotor capabilities and loss of modulatory brain functions can be observed.…”
Section: Introductionmentioning
confidence: 99%